2017
DOI: 10.1038/hr.2017.89
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation does not affect ankle–brachial index measured using the Doppler method

Abstract: Atrial fibrillation may affect blood pressure measurements. The ankle-brachial index (ABI) is a ratio of systolic blood pressure measured on the lower and upper limbs that may also be affected by arrhythmia. The purpose of the study was to investigate whether atrial fibrillation influenced ABI results. Ninety-nine patients (age 66.6±11 years, 63 males and 36 females) who underwent electrical cardioversion of atrial fibrillation were investigated. ABI measurements using the Doppler method were performed on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Atrial fibrillation may substantially influence blood pressure measurements. Previously, we found that the results of ABI measured using the Doppler method during atrial fibrillation corresponded with the results obtained in sinus rhythm [9].…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Atrial fibrillation may substantially influence blood pressure measurements. Previously, we found that the results of ABI measured using the Doppler method during atrial fibrillation corresponded with the results obtained in sinus rhythm [9].…”
supporting
confidence: 66%
“…In this study, we included data from one hundred and fifteen consecutive patients with atrial fibrillation admitted for electrical cardioversion (EC). The current study is the extension of the research published by Dabrowski et al [9], where detailed patients' characteristics were presented. Ninety-nine patients (mean age: 66.6 ±11) years, M/F − 63/36) underwent the complete study protocol and were analyzed ( Figure 1).…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…1. Preoperative stage: the informed consent process was conducted, the ABI was measured using a handheld Doppler probe and calculated as previously described, 7 and the general anamnesis and routine laboratory values were taken. 2.…”
Section: Data Collection Methodsmentioning
confidence: 99%